2021
DOI: 10.1186/s12913-021-06628-5
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and the acceptance of innovations in technology-intensive contexts: the need for tailored management strategies

Abstract: Background Several technological innovations have been introduced in healthcare over the years, and their implementation proved crucial in addressing challenges of modern health. Healthcare workers have frequently been called upon to become familiar with technological innovations that pervade every aspect of their profession, changing their working schedule, habits, and daily actions. Purpose An in-depth analysis of the paths towards the acceptance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…Also, according to the results of this study, two factors; "the need for high experience and skill to work with technologies" and "the need for a coach while using technologies", are the main factors related to "low self-con dence when dealing with technologies" that increase the technophobia of nursing students. This nding con rms the results of a study [45,46] which states that it is more di cult for nurses who are less con dent in their skills and abilities to face and work with new technology.…”
Section: Discussionsupporting
confidence: 84%
“…Also, according to the results of this study, two factors; "the need for high experience and skill to work with technologies" and "the need for a coach while using technologies", are the main factors related to "low self-con dence when dealing with technologies" that increase the technophobia of nursing students. This nding con rms the results of a study [45,46] which states that it is more di cult for nurses who are less con dent in their skills and abilities to face and work with new technology.…”
Section: Discussionsupporting
confidence: 84%
“…This may reflect higher self-reported digital competence among younger HCP which was indicated in a study of 27 UK primary care facilities (Hammerton et al, 2022). A recent Italian study by Barchielli et al (2021) investigating nurses' acceptance of innovations in technology-intensive contexts also supports the hypothesis of age as a key factor in the nursing-technology context. They found that age is a key moderator for social influence and that older nurses appeared to be influenced less by social factors.…”
Section: Agementioning
confidence: 77%
“…Furthermore, technology-based innovations can provide new insights for nurses, increase knowledge, and skills in providing nursing interventions. The results of previous studies indicate that with technology-based innovations as well as being innovative and application, it can increase the knowledge and skills of nurses (Asurakkody & Shin, 2018;Barchielli et al, 2021). However, with training related to the use of innovative technology that will be developed, nurses need to equalize perceptions and abilities in using these applications.…”
Section: Original Articlementioning
confidence: 99%